Prevention of Preterm Labour: 2011 Update on Tocolysis - C. Hubinont; F. Debieve (Journal of Pregnancy)
The aim of this paper is to review available data about drugs for preventing preterm labour. Tocolytic therapy includes β adrenergic receptor agonists, NO donors, magnesium sulphate, prostaglandin-synthase inhibitors, oxytocin receptor antagonists, calcium-channel blockers, progesterone, 17-α-hydroxyprogesterone caproate, and antibiotics. Their specific effects on myometrial contractility, their safety, their efficiency, and side effects profile for the mother and the fetus are presented. The main question of why and for what reasons tocolysis should be administrated is discussed.